Do Fixed Exchange Rates Induce More Fiscal Discipline? - Sun, Yan (IMF Working Papers; Working Paper ;, 2003)
Conventional wisdom has held that a fixed exchange rate regime induces more fiscal discipline, but Tornell and Velasco (1995, 1998) argue the opposite. Using a dynamic model with fragmented fiscal policymaking, this paper evaluates the two arguments in a single framework and shows that (1) future punishment against fiscal laxity exists under both fixed and flexible regimes; (2) fiscal authorities have a greater incentive to spend more today under fixed rates than under flexible rates; (3) in the presence of both factors above, fixed rates will induce more fiscal discipline only if the future punishment is sufficiently stronger than under flexible rates; and (4) neither fixed nor flexible rates could resolve the structural distortions caused by fragmented policymaking, and fiscal centralization needs to be undertaken to strengthen fiscal discipline.